Comprehensive monitoring of Bangladesh tree cover inside and outside of forests, 2000–2014. (18th October 2017) - Potapov, P; Siddiqui, B N; Iqbal, Z; Aziz, T; Zzaman, B; Islam, A; Pickens, A; Talero, Y; Tyukavina, A; Turubanova, S; Hansen, M C
Abstract: A novel approach for satellite-based comprehensive national tree cover change assessment was developed and applied in Bangladesh, a country where trees outside of forests play an important role in the national economy and carbon sequestration. Tree cover change area was quantified using the integration of wall-to-wall Landsat-based mapping with a higher spatial resolution sample-based assessment. The total national tree canopy cover area was estimated as 3165 500 ± 186 600 ha in the year 2000, with trees outside forests making up 54% of total canopy cover. Total tree canopy cover increased by 135 700 (± 116 600) ha (4.3%) during the 2000–2014 time interval. Bangladesh exhibits a national tree cover dynamic where net change is rather small, but gross dynamics significant and variable by forest type. Despite the overall gain in tree cover, results revealed the ongoing clearing of natural forests, especially within the Chittagong hill tracts. While forests decreased their tree cover area by 83 600 ha, the trees outside forests (including tree plantations, village woodlots, and agroforestry) increased their canopy area by 219 300 ha. Our results demonstrated method capability to quantify tree canopy cover dynamics within a fine-scale agricultural landscape. Our approach for comprehensive monitoring of tree canopy cover may be recommended for operational implementation in Bangladesh and other countries with significant tree cover outside of forests.